(untitled) (ҚазҰУ Хабаршысы. Дінтану сериясы, 2020)
Today, Islamic philosophy raises a number of pressing issues. Of these, the most discussed is the "Arabic reason." Many scholars and philosophers of the Islamic world wrote on this subject. One of them is Muhammad Abid Jabiri - the author of the work «Critique of the Arabic reason» consisting of 4 volumes. In the first part of the article, the authors will try to reveal the personality of the philosopher based on his personal, scientific and political life. The second part of the article examines his book, The Formation of the Arabic reason, which is the first volume of Critique of the Arabic reason. Since acquaintance with the biography of the scholar and his works will help in understanding his philosophical views. Muhammad Jabiri has been striving all his life to develop Islamic philosophy and revise its epistemological structure. In 1982, he wrote The Formation of the Arabic reason, 1986 the Structure of the Arabic reason, 1990 the Political Arabic reason, and 2001 the Practical Arabic reason. These four volumes of «Critique of the Arabic reason» have been widely disseminated and are discussed to this day. Also, quite a few critics came to his address. Some of them are mentioned here in brief. At the end is a list of literatures written on the subject of «Arabic reason».